2017
DOI: 10.1128/jcm.01573-16
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Urinary Antigen Detection for 13 Streptococcus pneumoniae Serotypes Improves Diagnosis of Pneumococcal Pneumonia in South African HIV-Infected Adults

Abstract: A serotype-specific urinary antigen detection (UAD) assay for 13 serotypes included in the pneumococcal conjugate vaccine (PCV13) was recently reported as a useful diagnostic tool for pneumococcal pneumonia. We aimed to assess the diagnostic accuracy of the UAD in HIV-infected South African adults. Urine specimens from a well-defined cohort of HIV-infected South African adults with pneumonia were evaluated retrospectively in the UAD assay. Pneumonia was considered pneumococcal if either sputum Gram stain, sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Further studies are needed to describe the serotype distribution of pneumococcal pneumonia in Malawi, to determine whether targeted vaccination programs of at-risk groups may be beneficial to tackle the persistent burden of adult disease. Recently developed urinary assays that can detect serotype-specific antigens in noninvasive pneumococcal pneumonia may provide a more comprehensive description (47).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to describe the serotype distribution of pneumococcal pneumonia in Malawi, to determine whether targeted vaccination programs of at-risk groups may be beneficial to tackle the persistent burden of adult disease. Recently developed urinary assays that can detect serotype-specific antigens in noninvasive pneumococcal pneumonia may provide a more comprehensive description (47).…”
Section: Discussionmentioning
confidence: 99%
“…68 A South African study confirmed that ss-UAD has high diagnostic accuracy to detect pneumococcal pneumonia and simultaneous detection of PCV13 serotypes in HIV-infected adults in South Africa, offering a potentially useful tool to determine pneumococcal pneumonia in this population. 69 Of note is the persistence of ST3 as one of the most prevalent vaccine serotypes both before and after the PCV13 infant programme. A recent global genomic analysis of ST3 has identified a new antibiotic-resistant clade which is replacing the less resistant clade.…”
Section: Discussionmentioning
confidence: 99%
“… 68 A South African study confirmed that ss-UAD has high diagnostic accuracy to detect pneumococcal pneumonia and simultaneous detection of PCV13 serotypes in HIV-infected adults in South Africa, offering a potentially useful tool to determine pneumococcal pneumonia in this population. 69 …”
Section: Discussionmentioning
confidence: 99%
“…Sputum is generally considered a better sample as compared to NP swabs (sensitivity 78-94% vs 44-81%, specificity 80-87% vs 80-99%, AUC-ROC 0,80-0.96 vs 0.80-0.86) [22][23] [24]. However, the few reports which have compared rtPCR-lytA in sputum and NP samples came to conflicting results: two of them found that sputum had higher sensitivity [22] [24] while another one observed a comparable diagnostic performance between sputum and NP swabs [23]. However, obtaining a good-quality sputum is not easy as many pneumonia patients have a dry cough and are unable to produce sputum.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort adequate sputum could be obtained in less than one third of cases and P-CAP could be diagnosed using sputum as diagnostic test in only 10% of cases. As previously described [23], NP swab may be preferable for the diagnosis of P-CAP as it can be collected in all patients.…”
Section: Discussionmentioning
confidence: 99%